Systemic-to-pulmonary artery shunting using heparin-bonded grafts - Ambarsari, Yuletta Adny; Purbojo, Ariawan; Blumauer, Robert; Glöckler, Martin; Toka, Okan; Cesnjevar, Robert; Rueffer, Andre (Interactive Cardiovascular and Thoracic Surgery, 2018)
OBJECTIVES: Systemic-to-pulmonary artery shunting remains an important palliative procedure in the staged management of complex congenital heart defects. The use of heparin-bonded polytetrafluoroethylene shunts (HBPSs) should enhance graft patency. This study aimed to review the single-centre experience using HBPS in the context of congenital cardiac surgery. METHODS: The records of 51 patients treated using HBPS between 2010 and 2016 were retrospectively reviewed. The median age and weight of the patients were 8 (range 3-83) days and 3.2 (range 1.8-5.7) kg, respectively. Selected shunt size was 3.5 mm in all patients. Fourteen (27.5%) patients were planned for future biventricular repair and 37 (72.5%) patients underwent univentricular pathway. Shunt modifications included central aortopulmonary shunts (n = 35; 68.6%) and modified Blalock-Taussig shunts (n = 16; 31.4%). Shunt patency and survival until estimated 2nd procedure were calculated using the Kaplan-Meier method. RESULTS: Shunt patency was 90 ± 4% after a median duration of 133 (range 0-315) days. Early mortality (30 days) was 3.9% (n = 2). Another 3 patients died during their hospital stay. All the deceased patients had univentricular morphology, and the cause of death was not shunt related in all patients. Five patients developed subtotal HBPS thrombosis intraoperatively (n = 3), early postoperatively after 3 days (n = 1, 1.9%) or late after 41 days (n = 1, 1.9%). Treatment of those patients comprised right ventricular outflow tract opening (n = 2, 3.9%) or new shunting (n = 3, 5.9%). Elective shunt takedown was performed during corrective surgery (n = 10, 19.6%), bidirectional Glenn (n = 25, 49%) or shunt replacement (n = 5, 9.8%). At the end of follow-up, 1 (1.9%) patient had still an HBPS in situ. The survival rate until planned 2nd procedure was 87 ± 6% in univentricular patients and 100% in biventricular patients (P = 0.17). CONCLUSIONS: The use of HBPS in the context of palliative heart surgery is safe and seems to warrant a long-term patency of systemic-to-pulmonary shunts. However, by acting on only 1 site of Virchow's triad, shunt thrombosis, occurring predominantly early, cannot be totally excluded.
EVALuna2:35480